Gizi Anak Usia Sekolah Ceria Cegah Anemia Remaja Dengan Imbangan Asupan - Egy Sunanda Putra; Rusmimpong Rusmimpong; Alpari Nopindra (Barongko: Jurnal Ilmu Kesehatan, 2026)
ABSTRACT The high risk of anemia among female students at SMA Negeri 5 in Jambi City reflects a serious nutritional problem. Many students experience symptoms such as dizziness, weakness, nausea, and abdominal pain, which are directly related to anemia and nutritional imbalance. Dizziness and weakness can indicate iron deficiency, especially in adolescent girls. Complaints of nausea and heartburn indicate irregular eating patterns, which result in low intake of essential nutrients. Lack of knowledge about anemia and balanced nutrition is a major factor influencing unhealthy eating patterns among adolescents. To address this, educational interventions were conducted through education on anemia and balanced nutrition using Battle Quizzes and Kahoot! quizzes, the introduction of the "Isi Piringku" concept as a visual guide to healthy eating, and the establishment of the "Pojok Sehat CERIA" as a health information center at the school. Furthermore, a "Pojok Sehat CERIA" (CERIA Health Content Competition) was held with the theme of anemia and balanced nutrition. The winner will be crowned as a CERIA friend ambassador. These "CERIA friend ambassadors" will serve as role models for students and will continue the efforts of the Pojok Sehat CERIA. This activity was conducted from April 28–May 20, 2025, and involved 10th-grade students. Evaluation showed a significant increase in students' knowledge and awareness regarding the importance of a balanced, nutritious diet and anemia prevention. This visual-based, participatory intervention proved effective and could be adapted as a promotive-preventive effort for adolescent health in other schools. Keywords: Balanced Nutrition, Anemia, Adolescents, Nutrition Education, My Plate, Health Promotion. ABSTRAK Tingginya risiko anemia di kalangan siswi SMA Negeri 5 Kota Jambi mencerminkan permasalahan gizi yang serius, dengan banyak siswa mengalami gejala seperti pusing, lemas, mual, dan sakit perut, merupakan gejala yang berhubungan langsung dengan anemia dan ketidakseimbangan gizi. Pusing dan lemas bisa mengindikasikan kekurangan zat besi, terutama pada remaja putri. Keluhan mual dan maag menunjukkan pola makan yang tidak teratur, yang berdampak pada rendahnya asupan nutrisi penting. Kurangnya pengetahuan tentang anemia dan gizi seimbang menjadi faktor utama yang memengaruhi pola makan tidak sehat di kalangan remaja. Untuk mengatasi hal ini, dilakukan intervensi edukatif melalui edukasi Anemia dan Gizi Seimbang dengan Battle Quizz dan juga kuis Kahoot!, pengenalan konsep “Isi Piringku” sebagai panduan visual makan sehat, pembentukan “Pojok Sehat CERIA” sebagai pusat informasi kesehatan di sekolah. Lalu mengadakan “Lomba Konten Kesehatan CERIA” dengan tema Anemia dan Gizi Seimbang, dimana pemenangnya akan dinobatkan sebagai duta sahabat CERIA. “Duta Sahabat CERIA” tersebut akan menjadi role model bagi siswa/i dan akan meneruskan Pojok Sehat CERIA. Kegiatan ini dilaksanakan pada 28 April–20 Mei 2025 dan melibatkan siswa kelas X. Evaluasi menunjukkan adanya peningkatan signifikan dalam pengetahuan dan kesadaran siswa mengenai pentingnya pola makan bergizi seimbang dan pencegahan anemia. Intervensi berbasis visual dan partisipatif ini terbukti efektif dan dapat diadaptasi sebagai upaya promotif-preventif kesehatan remaja di sekolah lain. Kata Kunci: Gizi seimbang, anemia, remaja, edukasi gizi, Isi Piringku, promosi kesehatan.